Ulrich Bielefeld: Aliens - Friends or Enemies.: (from the Serbian translation) Stranci – prijatelji ili neprijatelji, Bibilioteka XX vek, Beograd 1998 - Muhič-Dizdarevič, Selma (Lidé města, 2005)
A review of the book by Ulrich Bielefeld.